Student readers' use of library documents: Implications for digital library technologies - Sellen, Abigail; O'Hara, Kenton (Proceedings of CHI '98, ACM, New York, 1998)
We report on a study of graduate students conducting research in libraries, focusing on how they extract and record information as they read. By examining their information recording activities within the context of their work as a whole, it is possible to highlight why students choose particular strategies and styles of recording for what these activities provide both at the time of reading and at subsequent points in time. The implications of these findings for digital library technologies are discussed.